PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PT. BANK BNI TBK CABANG PAMEKASAN YANG DIMEDIASI OLEH KOMITMEN ORGANISASI - Eko Febriyanto; Chamariyah Chamariyah (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
The aims of this study are o test and analyze motivation effect on employee performance which is mediated by organizational commitment. The results showed that Motivation has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.286 and the p-values ​​of 0.007. Motivation has a positive and significant effect on organizational commitment. This is evidenced by the original sample value of 0.501 and the p-values ​​of 0.000. Organizational commitment has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.429 and the p-values ​​of 0.000. Motivation has a significant positive effect on employee performance mediated by organizational commitment. This is evidenced by the original sample value of 0.215 and the p-values ​​of 0.002.